A Method to Assess Groundwater Vulnerability to depletion in Alluvial plain, Jilin, China - Elkrail Adil; SHU Long-Cang (International Journal of Research in Chemistry and Environment (IJRCE), 2012)
The Quantitative Groundwater Vulnerability Assessment (GVA) method was developed and tested to provide vulnerability index maps to groundwater depletion. GIS technique was used to create these maps. A numerical ranking scheme is used to assess groundwater risk in varying geologic settings. The parameters used for vulnerability assessment of groundwater quantity in the Songhuajiang river valley, China, are aquifer thickness, drawdown, groundwater pumping density and net recharge. The GVA method was manipulated by using percentage ratio parameters and separated parameters to create two quantitative groundwater vulnerability assessment index maps and to choose which is the best method should be adopted to evaluate the quantitative groundwater vulnerability assessment (GVA). The percentage ratio parameters index map classifies 27% (score 0 5) of the study area as more safe and having least vulnerability to depletion, 46% (score 5 11) as having moderate vulnerability to depletion, whereas 27% (score 11 16) as having most vulnerability to depletion. The separated parameters index map classifies 25% (score 7 14) of the study area as having least vulnerability, 49% (score 14 20) as having moderate vulnerability whereas 26% (score 20 27) as having most vulnerability to depletion.